CGIAR's Role in Shaping Climate Action at COP29: Key Tracks and Contributions - CGIAR Climate Impact Platform (CGIAR System Organization, 2024)
A cohesive global strategy is crucial to meet the climate goals and agreements. CGIAR emphasizes the importance of enhancing institutional alignment, refining financing frameworks, and expanding technical assistance to support country-led adaptation plans and investment pipelines. Strategic partnerships can strengthen governance and facilitate the use of technical cooperation platforms, streamlining efforts across food, land, and water systems. By prioritizing coordinated action, CGIAR seeks to empower smallholder farmers, enhance resilience, and contribute to a sustainable transformation of food systems in line with the Paris Agreement.